Analisis Strategi Konten YouTube Pusbiola dalam Berbagi Informasi dan Pengetahuan - Nasrullah (Ikatan Pustakawan Indonesia, 2022)
All library organizations are compelled to reevaluate how they manage material that is retained for public distribution due to the current development of information. In the modern information era, a strategy that maximizes information and communication technologies and new media to disseminate all of the information or material that the library holds has arisen. One of the new media utilized as a platform is YouTube, which offers an attractive opportunity for people or organizations like Pusbiola to transmit information and expertise with a larger audience via the use of information technology in the social media era. This research will investigate Pusbiola's content strategy for distributing information and knowledge on YouTube. A descriptive, qualitative technique is employed in the data collecting process, which includes internet data searches, and observation. The study's results show how successful Pusbiola's content strategy using YouTube social media is at building the organization's brand, and by arranging and taking into consideration the dispersed materials, the reach of knowledge exchange may be enhanced.. The findings suggest that there are still issues with implementing content production strategies that are developed with a range of target audiences and have not established screening or quality control for material to be published on YouTube social media